HDL mimetic peptide CER-522 treatment regresses left ventricular diastolic dysfunction in cholesterol-fed rabbits. (15th July 2016) - Merlet, Nolwenn; Busseuil, David; Mihalache-Avram, Teodora; Mecteau, Melanie; Shi, Yanfen; Nachar, Walid; Brand, Genevieve; Brodeur, Mathieu R.; Charpentier, Daniel; Rhainds, David; Sy, Gavin; Schwendeman, Anna; et al.
Abstract: Objectives: High-density lipoprotein (HDL) infusions induce rapid improvement of experimental atherosclerosis in rabbits but their effect on ventricular function remains unknown. We aimed to evaluate the effects of the HDL mimetic peptide CER522 on left ventricular diastolic dysfunction (LVDD). Methods: Rabbits were fed with a cholesterol- and vitamin D2 -enriched diet until mild aortic valve stenosis and hypercholesterolemia-induced LV hypertrophy and LVDD developed. Animals then received saline or 10 or 30 mg/kg CER522 infusions 6 times over 2 weeks. We performed serial echocardiograms and LV histology to evaluate the effects of CER522 therapy on LVDD. Results: LVDD was reduced by CER-522 as shown by multiple parameters including early filling mitral deceleration time, deceleration rate, Em/Am ratio, E/Em ratio, pulmonary venous velocities, and LVDD score. These findings were associated with reduced macrophages (RAM-11 positive cells) in the pericoronary area and LV, and decreased levels of apoptotic cardiomyocytes in CER522-treated rabbits. CER-522 treatment also resulted in decreased atheromatous plaques and internal elastic lamina area in coronary arteries. Conclusions: CER522 improves LVDD in rabbits, with reductions of LV macrophage accumulation, cardiomyocyte apoptosis, coronary atherosclerosis and remodelling. Highlights: HDL mimetic CER-522 infusions regress experimental LV diastolic dysfunction. CER-522 reduced macrophage accumulation in the pericoronary area and left ventricle. CER-522-treated rabbits had decreased levels of apoptotic cardiomyocytes. Treatment also resulted in decreased coronary plaques and vascular remodelling.